Dual effects of human neutrophil peptides in a mouse model of pneumonia and ventilator-induced lung injury - Zheng, Junbo (Respir Res, 2018)
BACKGROUND: Pneumonia is a major cause of high morbidity and mortality in critically illness, and frequently requires support with mechanical ventilation. The latter can lead to ventilator-induced lung injury characterized by neutrophil infiltration. The cationic human neutrophil peptides (HNP) stored in neutrophils can kill microorganisms, but excessive amount of HNP released during phagocytosis may contribute to inflammatory responses and worsen lung injury. Based on our previous work, we hypothesized that blocking the cell surface purinergic receptor P2Y(6) will attenuate the HNP-induced inflammatory responses while maintaining their antimicrobial activity in pneumonia followed by mechanical ventilation. METHODS: Plasma HNP levels were measured in patients with pneumonia who received mechanical ventilation and in healthy volunteers. FVB littermate control and HNP transgenic (HNP(+)) mice were randomized to receive P. aeruginosa intranasally. The P2Y(6) antagonist (MRS2578) or vehicle control was given after P. aeruginosa instillation. Additional mice underwent mechanical ventilation at either low pressure (LP) or high pressure (HP) ventilation 48 h after pneumonia, and were observed for 24 h. RESULTS: Plasma HNP concentration increased in patients with pneumonia as compared to healthy subjects. The bacterial counts in the bronchoalveolar lavage fluid (BALF) were lower in HNP(+) mice than in FVB mice 72 h after P. aeruginosa instillation. However, upon receiving HP ventilation, HNP(+) mice had higher levels of cytokines and chemokines in BALF than FVB mice. These inflammatory responses were attenuated by the treatment with MRS2578 that did not affect the microbial effects of HNP. CONCLUSIONS: HNP exerted dual effects by exhibiting antimicrobial activity in pneumonia alone condition while enhancing inflammatory responses in pneumonia followed by HP mechanical ventilation. Blocking P2Y(6) can attenuate the inflammation without affecting the antibacterial property of HNP. The P2Y(6) receptor may be a novel therapeutic target in attenuation of the leukocyte-mediated excessive host responses in inflammatory lung diseases.